Syncope as a dominant symptom of pulmonary embolism - a case report - Baralic, Marko B; Mitić, Javorka; Đurđević, Nataša; Janković, Jelena; Vešović, Radomir; Jordanova, Elena; Tabaković, Dejan; Janković, Radmila (Halo 194 Scientific Journal of Emergency Medicine, 2020)
AbstractPulmonary embolism (PE) and deep vein thrombosis (DVT) may be an associated clinical syndrome that results from a single entity which is venous thrombo-embolism (VTE).            In most patients, pulmonary embolism is manifested by a specific triad of symptoms in the form of dyspnea, pleurodynia and tachycardia, while syncope is rare, with an incidence of 6% in all patients. Since syncope with mild dyspnoea was the dominant symptom in our patient, PE was difficult to suspect, which is why additional diagnostics were performed in the form of Doppler ultrasonography of the lower extremities and multislice angiography of the pulmonary artery, which detected the disease and confirmed the diagnosis.Even though it is a common clinical symptom,  syncope is most often associated with neurological or cardiac events, but it is still a crossroad of various internal diseases because it can also be presented in lung diseases. Keywords: sincopa, embolism, thrombosis